2014
DOI: 10.4236/ojneph.2014.42011
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Burden on Family Carers of Hemodialysis Patients

Abstract: Background: Hemodialysis (HD) is an important objective burden (task) on patient with end stage renal disease (ESRD) and the caregiver has a subjective burden which contributes to lifestyle changes, which result in depression, anxiety declining physical health, social isolation and financial strain. Aim: To evaluate the subjective burden on family caregiver who cares patient on maintenance hemodialysis therapy. Methods: Fifty main family caregivers for each patient on HD and the instrument were used by Caregiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
79
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(96 citation statements)
references
References 20 publications
11
79
3
3
Order By: Relevance
“…Caregivers with higher education (>10 years of formal edu- Pearson Correlation *p significant at ≤ 0.05 level of significance cation) were found to have significantly less burden. This finding is in accordance to a study done in Saudi Arabia which showed statistically significant negative correlation between caregiver burden and caregiver education [8]. It is a general consideration that increased education and awareness about a disease condition may make it more tolerable for patients and their families [4].…”
Section: Socio-demographic Variables Of Caregivers and Caregiver Burdensupporting
confidence: 80%
See 3 more Smart Citations
“…Caregivers with higher education (>10 years of formal edu- Pearson Correlation *p significant at ≤ 0.05 level of significance cation) were found to have significantly less burden. This finding is in accordance to a study done in Saudi Arabia which showed statistically significant negative correlation between caregiver burden and caregiver education [8]. It is a general consideration that increased education and awareness about a disease condition may make it more tolerable for patients and their families [4].…”
Section: Socio-demographic Variables Of Caregivers and Caregiver Burdensupporting
confidence: 80%
“…This may be because it is difficult for the older caregivers to travel and manage treatment for their patients as compared to the younger caregivers. However, this finding is contradicted in literature as the caregiver burden was found to be significantly higher in younger than in older caregivers [8,10]. In more developed countries like Turkey and Saudi Arabia where these researches are carried out, the facilities of transportation and health care may have made it easier for the older caregivers in providing health care to their patients.…”
Section: Socio-demographic Variables Of Caregivers and Caregiver Burdencontrasting
confidence: 54%
See 2 more Smart Citations
“…Dialysis population is becoming older and older [4] and has an increased risk of physical, cognitive, and emotional deterioration [5], due to diabetes, hypertension, cardiovascular risk factors, pulmonary and skeletal problems [4], and multiple metabolic disturbances [5], with their mobility and ability to self-care being negatively afected. Thus, elderly dialysis patients need care not only from health professionals but also from caregivers, including spouses, parents, brothers and sisters, friends, as well as emotionally involved volunteers [4].…”
Section: Introductionmentioning
confidence: 99%